2023
DOI: 10.1007/s10518-023-01782-z
|View full text |Cite
|
Sign up to set email alerts
|

Seismic behaviour of reinforced-masonry aggregate under different types of interaction between adjacent dwellings

Sebastian Torres-Olivares,
Beatriz González-Rodrigo,
Erick I. Saavedra-Flores
et al.

Abstract: Assessing the seismic vulnerability of existing buildings is an essential task for the management of earthquake disasters. For this purpose, the seismic behaviour of buildings is usually determined under the assumption of isolated conditions, although aggregate structures are one of the most common typologies found in urban centres. This study aims to investigate the nonlinear static behaviour of aggregate dwellings consisting of grouted reinforced concrete block configurations commonly observed in San José, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Furthermore, the difficulty involved in adequately connecting the two construction systems underlies the fact that many buildings presented damage resulting from sliding between lower walls and upper floors of differing materials (Figure 15b). Additionally, the positioning of these dwellings within the aggregate might influence their seismic response [38][39][40].…”
Section: Structural Damage In Traditional Construction Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the difficulty involved in adequately connecting the two construction systems underlies the fact that many buildings presented damage resulting from sliding between lower walls and upper floors of differing materials (Figure 15b). Additionally, the positioning of these dwellings within the aggregate might influence their seismic response [38][39][40].…”
Section: Structural Damage In Traditional Construction Systemsmentioning
confidence: 99%
“…Previous seismic events and research into these events have shown the importance of the position in the block [40,[46][47][48][49][50] and the pounding effects [38,51] between adjacent buildings on the seismic vulnerability. The seismic performance of masonry building aggregates is often affected by the presence of fragile and deformable floor membranes, along with asymmetrical geometries.…”
Section: Urban Positionmentioning
confidence: 99%